2014
DOI: 10.1155/2014/658205
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Wealth and Health in Insurance Choice: Bivariate Probit Analysis in China

Abstract: This paper captures the correlation between the choices of health insurance and pension insurance using the bivariate probit model and then studies the effect of wealth and health on insurance choice. Our empirical evidence shows that people who participate in a health care program are more likely to participate in a pension plan at the same time, while wealth and health have different effects on the choices of the health care program and the pension program. Generally, the higher an individual’s wealth level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…A study in SSA by Barasa et al found that wealthier individuals were more likely to have a health insurance compared to those with less income [2]. Generally, the higher an individual’s wealth level is, the more likelihood he will participate in a health care program in SSA [2] [19] [20] and this is similar to what was observed in China, Spain and USA [18] [21] [22] [23] [24]. The implication of the association between wealth and insurance uptake for settings like Malawi would be to consider a minimal amount of health insurance schemes for the less privileged since the less privileged are the most marginalized in uptake of health insurance.…”
Section: Discussionmentioning
confidence: 58%
“…A study in SSA by Barasa et al found that wealthier individuals were more likely to have a health insurance compared to those with less income [2]. Generally, the higher an individual’s wealth level is, the more likelihood he will participate in a health care program in SSA [2] [19] [20] and this is similar to what was observed in China, Spain and USA [18] [21] [22] [23] [24]. The implication of the association between wealth and insurance uptake for settings like Malawi would be to consider a minimal amount of health insurance schemes for the less privileged since the less privileged are the most marginalized in uptake of health insurance.…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, individuals' income is related to their health status, and those with a better self-rated health status are generally more likely to be employed and to have a sustained income than those with a poor self-rated health status. If they feel their future income is not sustainable and the premiums are not affordable, they may not choose to purchase private medical insurance (Yue and Zou, 2014). There is another reason for self-rated health status as a mediator.…”
Section: Mediating Role Of Self-rated Health Statusmentioning
confidence: 99%
“…Another study found that eastern provinces were associated with greater income from PHI premiums per capita than central or western inland provinces, other things being equal [47]. Two nationwide studies found that urban residents were more likely to be covered by PHI than rural residents, other things being equal [41,48]. Another multi-province study found that students living in urban areas were more likely to have PHI than non-students, but this phenomenon was found to disappear in rural areas [32].…”
Section: Trend and Distributionmentioning
confidence: 99%